Exploring the Influence of Parental Interaction on Consumptive Behavior: The Mediating Role of Self-Control Among Santri - Maulana Achsan Al Farisi; Yulina Eva Riany; Lilik Noor Yuliati (Program Pascasarjana Universitas Ibrahimy, 2025)
Santri in Islamic boarding schools (pesantren) are expected to uphold values of simplicity and self-discipline. However, increasing exposure to consumerist culture has challenged these ideals, leading to a rise in consumptive behavior among santri-college students. This study investigates how parental interaction influences consumptive behavior, with self-control acting as a mediating factor. Grounded in a quantitative approach, the study involved 237 santri aged 18–23 years in Yogyakarta, selected through Cluster Random Sampling and refined via Purposive Sampling based on defined criteria. Validated instruments were used to measure parental interaction (Cronbach’s Alpha = 0.85), self-control (α = 0.85), and consumptive behavior (α = 0.96). Data analysis using Structural Equation Modeling (SEM) revealed that while parental interaction does not directly reduce consumptive behavior (p = 0.080), it significantly enhances self-control (p < 0.001), which in turn negatively correlates with consumptive behavior (p < 0.001). These findings underscore the critical role of self-control as a mediator and suggest that strengthening parental interaction may indirectly reduce consumptive tendencies. This research contributes to educational and psychological strategies that support the development of financially wise, disciplined santri aligned with pesantren values.